2015
DOI: 10.1007/10_2015_313
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies in Molecular Imprinting

Abstract: This chapter introduces the basic principle and the synthetic aspects of molecular imprinting. First, the use of a molecular template to guide the location of functional groups inside molecularly imprinted cavities is explained. Three different mechanisms that ensure a molecular template associates with functional monomers or the imprinted polymers, that is, through reversible covalent, noncovalent, and sacrificial covalent bonds, are then described. The main focus is put on noncovalent molecular imprinting us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…The high binding of MX2 CAF is indicative of the formation of higher concentration of T-fM complexes as a result of higher concentration of functional monomer incorporated in the polymer. The lower binding exhibited by MX10 CAF polymers is consistent with the published results of Yoshimatsu et al [ 24 ] which, they also attributed to the lower concentration of T-fM complexes formed during the imprinting process [ 16 , 24 , 57 , 58 , 59 ]. Figure 4 b also showed that MX2 THP incorporated the highest THP (177.3 ± 1.3 µmol/g) for this system, and incorporation of THP decreased by 3.9 times to 45.9 ± 0.1 µmol/g in MX10 THP polymers.…”
Section: Resultssupporting
confidence: 90%
“…The high binding of MX2 CAF is indicative of the formation of higher concentration of T-fM complexes as a result of higher concentration of functional monomer incorporated in the polymer. The lower binding exhibited by MX10 CAF polymers is consistent with the published results of Yoshimatsu et al [ 24 ] which, they also attributed to the lower concentration of T-fM complexes formed during the imprinting process [ 16 , 24 , 57 , 58 , 59 ]. Figure 4 b also showed that MX2 THP incorporated the highest THP (177.3 ± 1.3 µmol/g) for this system, and incorporation of THP decreased by 3.9 times to 45.9 ± 0.1 µmol/g in MX10 THP polymers.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, to verify the binding site selectivity the imprinting factor “ IF ” was calculated. The IF factor is best defined as the ratio of the distribution ratio for the analyte on the MIPs to the distribution ratio for the same analyte on the NIPs 43 . It can be calculated using the following equation: …”
Section: Methodsmentioning
confidence: 99%
“…RAFT polymerization involves reversible addition-fragmentation sequences initiated by a FRP initiator and chain propagation is achieved with the help of a chain transfer agent. It can be used with a variety of functional groups and is suitable for non-covalent imprinting purposes [ 43 , 44 ].…”
Section: Polymerization Techniques For Mip Preparationmentioning
confidence: 99%